On the Exit of One Class of Random Walks from an Interval - Gusak, D. V. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We consider the random walk $S_n = \sum_{k\leqn}ξ_k \quad (S_n = 0)$ whose characteristic function of jumps $ξ_k$satisfies the condition of almost semicontinuity. We investigate the problem of the exit of such $S_n$ from a finite interval.